En Gender Issues in Greek-Turkish and Turkish-Greek Translation - Rompopoulou, Maria (International Journal of Language, Translation and Intercultural Communication, 2026)
This study explores gender-related issues in two languages: Greek, which has grammatical gender, and Turkish, a language without grammatical gender. The aim is to examine how the linguistic differences between these languages ​​ impact the translation process, particularly in terms of the translator’s performance and their understanding of gender. The research data presented and analyzed was collected through a combination of interviews with nine (9) participants, with many years of professional experience in the field of translation. Participants emphasized that a clear understanding of the text’s communicative purpose and the ability to accurately convey the author’s intentions are essential in dealing with gender issues in translation, often requiring the reformulation of original ideas. Moreover, the translators noted that a strong grasp of extra-linguistic factors— such as culture, traditions, and the political, social, and economic histories of Greece and Turkey— is crucial for any translator aiming to faithfully convey the meaning intended by the original author.